Assessment of climate change mitigation potential of the Kosovo energy and transport sector - Kabashi, Gazmend; Kola, Luan; Kabashi, Skender; Ajredini, Fadil (International Journal of Computational and Experimental Science and Engineering, 2024)
The Energy and transport sector in Kosovo are the main emitter of greenhouse gases (GHG) with a share of about 85% in total annual emissions. In energetic sector, 95-97% of emissions are associated with the electricity generation due to the predominant role of lignite fuelled power plants. The electricity sector contributes about 80% of total CO2 emissions in Kosovo. Those make the energy and transport sector the main emitters of CO2 and also the main target for CO2 emissions reduction. The National Energy and Climate Plan 2021-2030 aims to ensure a reliable supply of energy for Kosovo and proposes targets for renewable, energy efficiency, and greenhouse gas reductions. This paper presents analyses of different time frame scenarios for development of the Kosovo energy system in relation to climate change mitigation potential of the Kosovo energy and transport sector. The national energy system of Kosovo is modelled using EnergyPLAN software which integrates energy for electricity, transport and heat, and includes hourly fluctuations of energy demand and energy production. Three scenarios of Kosovo Energy system are modelled; starting point scenario 2019 and two long term scenarios 2030 with 23.3% and 41.8% share of renewable. An analysis of the overall energy system costs and security of supply with a main focus in electricity sector of the three scenarios is performed.